2020
DOI: 10.1016/j.omtm.2020.06.025
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9-Mediated In Vivo Gene Integration at the Albumin Locus Recovers Hemostasis in Neonatal and Adult Hemophilia B Mice

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 loaded by vectors could induce high rates of specific site genome editing and correct disease-causing mutations. However, most monogenic genetic diseases such as hemophilia are caused by different mutations dispersed in one gene, instead of an accordant mutation. Vectors developed for correcting specific mutations may not be suited to different mutations at other positions. Site-specific gene addition provides an ideal solution for long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Recent studies have successfully used site-specific targeted integration strategies to restore hemostasis in HB mouse models 9 . Site-specific integration of hF9 cDNA has been achieved through nuclease dependent or independent strategies, such as rAAV donor mediated HDR, ZFN or CRISPR/Cas9 stimulated HDR-mediated insertion to ameliorate hemophilia B in mouse models 9, 13, 32 . However, these studies showed a lower HDR efficiency in the adult liver compared with that in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have successfully used site-specific targeted integration strategies to restore hemostasis in HB mouse models 9 . Site-specific integration of hF9 cDNA has been achieved through nuclease dependent or independent strategies, such as rAAV donor mediated HDR, ZFN or CRISPR/Cas9 stimulated HDR-mediated insertion to ameliorate hemophilia B in mouse models 9, 13, 32 . However, these studies showed a lower HDR efficiency in the adult liver compared with that in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have successfully used site-speci c targeted integration strategies to restore hemostasis in HB mouse models 9 . Site-speci c integration of hF9 cDNA has been achieved through nuclease dependent or independent strategies, such as rAAV donor mediated HDR, ZFN or CRISPR/Cas9 stimulated HDR-mediated insertion to ameliorate hemophilia B in mouse models 9,13,32 . However, these studies showed a lower HDR e ciency in the adult liver compared with that in newborns.…”
Section: Discussionmentioning
confidence: 99%
“…
Figure 3 Viral vector-mediated in vivo therapeutic genome editing. (A) Schematic representation of dual AAV8 strategy for site-specific gene insertion in hepatocytes treating Hemophilia B 52 . Copyright Elsevier 2020.
…”
Section: Current Vectors For In Vivo Delivery Of Crispr-cas9 Therapeuticsmentioning
confidence: 99%